MODELING THE DIAMETER GROWTH OF PLANTED NATIVE TREES FOR THE RESTORATION OF MINED AREAS - Sousa, Vanessa Gomes de; Santana, Antônio Cordeiro; Júnior, Silvio Brienza; Hage, André Luis Ferreira; Barbosa, Maricélia Gonçalves; Salomão, Rafael Paiva (Floresta, 2024)
Tree diameter growth models of tree species are useful tools that allow monitoring the development of species and identifying whether the restored area is self-sustainable. The modeling can be expressed based on diameter growth data and represents an important parameter for predicting present and future diameters and assisting in decision-making in the forestry sector. This study aimed to develop a growth equation to estimate diameter growth rates for some planted native species and regenerated species in the restoration of mined areas. The performance of forest species was evaluated for 13 years for planted species, and eight years for the accompanying regeneration, and a regression model and analysis of variance were used, with diameter as the dependent variable. The adjusted parameters of the exponential model for each tree species resulted in a low standard error of the estimate of the coefficient b and significance at 95% for most of the species studied. The proposed model presented a good fit to the parameters of the equations and can be used to estimate the diameter of tree species and predict present and future production of forest stands, as long as the area conditions are similar to those of this study.